SEA DESCRIPTION IN HERMAN MELVILLE'S MOBY DICK - Andayani, Ambar (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Great literature is achieved through high imagination which needs big inspiration. Nature can be the power to create such great creation. Most of Melville's works are his works on his wanderings in the sea. Moby Dick is the famous one which tells about American whaling, that was popular in the 1840's. In his novel of Moby Dick, Melville reveals an extraordinary one which are full with emotive words and poetic language. His closeness with nature is reflected on Moby Dick. The sea gives him a power to reach universal idea for human being. As we find many philosophical commentary in this novel which conceives the truth for us. From the description and the explanation in this discussion, I can conclude that nature is the inspiration source in Herman Melville's Moby Dick.